An investigation for the efficacy of teaching model of combining virtual simulation and real experiment for clinical microbiology examination - Meng, Ling; Liu, Xia; Ni, Jing; Shen, Pei; Jiao, Fengping (Frontiers in Medicine, 2024)
Background As a convenient teaching tool, virtual simulation experiment technology had been widely utilized in the field of medical education. However, virtual learning could not fully replace the benefits of in-person instruction. Therefore, finding ways to integrate both methods was crucial for achieving optimal educational outcomes. The objective of this study was to compare the effectiveness of the self-built virtual simulation and design experiment combining teaching mode and the traditional experimental teaching mode in the clinical microbiology examination experiment teaching. Methods This study was conducted at Shandong First Medical University in China. The experimental group consisted of 100 third-year students from the grade 2020 majoring in medical examination technology, who underwent an innovative teaching model combining virtual and real experiments. The control group comprised of 100 third-year students from the grade 2019 in the same major, who received traditional experimental teaching model. In this study, we referred to grade 2020 as cohort 2020 and grade 2019 cohort 2019. The performance of both groups was assessed via experimental and theoretical testing. Meanwhile, survey questionnaires were administered to evaluate the efficacy of the innovative experimental teaching model and students’ level of satisfaction with it. Cohort 2020 conducted a survey for modules 1 to 4, while cohort 2019 only conducted a survey for module 4, as detailed in the Appendix. Results The majority of students in the experimental group expressed satisfaction with the teaching model that combined virtual and real experiments, as evidenced by their superior performance on both experimental operational skills (87.54 ± 8.93 vs. 82.39 ± 10.55) and theoretical knowledge tests (83.65 ± 9.02 vs. 80.18 ± 8.24) compared to those in the control group. Conclusion The combination of virtual simulation experiment and design experiment in the microbiological examination of clinical specimens represented an effective pedagogical approach. The instructional approach had the potential to incite a passion for learning, enhance proficiency in standardized experimental techniques, foster the ability to integrate theory with practice, and cultivate clinical reasoning skills.